BUILDING PERFORMANCE STANDARD AND ITS APPLICATION OF CONSTRUCTIVE DEMAND TO THE POST OCCUPANCY OF CONSTRUCTIONS: BUILDING PERFORMANCE STANDARD AND ITS APPLICATION OF CONSTRUCTIVE DEMAND TO THE POST OCCUPANCY OF CONSTRUCTIONS - Santos, Juliana Daniela Carla Sabino dos; Santos, White José dos; Martins, Cláudio José; Cesar, Cristina Guimarães (Brazilian Journal of Production Engineering, 2020)
The housing deficit in Brazil is a quantitative and qualitative problem. To combat this scenario, the government provides resources for building real estate and subsidies for the acquisition of housing. The release of these resources is subject to compliance with the requirements of NBR 15575: 2013, which establishes requirements and criteria in order to meet the requirements of users regarding safety, habitability and sustainability. This work aims to indicate the flow of housing production showing the context of use of NBR 15575: 2013 and indicate some official technical references made available to assist in its implementation. A flowchart was prepared containing the steps and agents involved in the construction process where it is possible to identify in which stages it is necessary to comply with the requirements indicated in the performance standard. Some measures are proposed that may contribute to the development of new FADs that present performance results from completed buildings. For improvements in the PSQs, actions are proposed that encourage the improvement and creation of new programs with an essentially technical character.